A Model for Managerial Ability Measurement with Emphasis on Accounting Constructs - Ghasem Blue; Manuchehr Roosta (بررسی‌های حسابداری و حسابرسی)
ObjectiveGiven that managers play a crucial role in grounded and old theories such as agency theory, stewardship theory, and contracts theory, the concept of managerial ability and its measurement has attracted the researchers' attention. Recent dominant perspective emphasizes that manager's ability is reflected in the firm's performance. Therefore, measuring managerial ability depends on the separation of the manager's performance from the firm's performance, and the more the manager's contribution to the company's performance, the higher ability he/she has. The current study seeks to develop a model to measure managerial ability, taking into account the unique circumstances of the country in which the companies operate.MethodsTo develop a model for measuring managerial ability, a comprehensive approach is applied including systematic literature review, interpretive analysis of interviews with experts, and a descriptive method. In systematic literature review domestic and foreign studies and reliable information sources and databases is applied based on specific related keywords. Additionally, interviews with experts such as executive managers, financial managers, internal and external auditors, and academics were analyzed using interpretive analysis based on chain sampling. To run and validate the designed model, data from 158 firms listed on the Tehran Stock Exchange (TSE) across 12 industries from 2012 to 2021 is used. Triangulation was employed to evaluate the research validity, considering multiple dimensions including methodology, data, and the researchers. This rigorous approach ensures the reliability and robustness of the model developed for measuring managerial ability.  ResultsAccording to the research findings, we focus on three areas of performance indicators (PI), namely operational, financing, and dividend performance indicators. The performance indicators, as dependent variable, represent different aspects of firm performance based on managers decision-making process and the status of firms in real world. Variables such as firm size, firm age, the percentage of active institutional shareholders, export sales, and transactions with related parties represent the inherent characteristics of each company as independent variables. Considering environmental conditions and performance indicators are very important in determining related variables. By running Tobit regression, the residual value is considered as managerial ability measurement or managers’ contribution in firm performance. Furthermore, the comparison of the designed model and the model developed by Demerjian et al. (2012), as the most widely used model in prior literature, in terms of log-likelihood and information criteria including Akaike Information Criterion (AIC), Schwarz Criterion (SC), and Hannan-Quinn Criterion (HQ) at the overall and industry-specific levels shows that our model has higher goodness-of-fit.ConclusionGenerally, by combining operational, financing, and profit distribution indicators, as well as taking into account shareholder structure and intra-group transactions, this model provides a more proper measurement of managerial effectiveness and it can be a basis for selecting managers and determining appropriate remuneration methods.